Kentucky folkmusic : an annotated bibliography - Feintuch, Burt, 1949-2018 (University Press of Kentucky, 1985)
In 1899, a fundraising program for Berea College featured a group of students from the mountains of eastern Kentucky singing traditional songs from their homes. The audience was entranced. That small en-counter at the end of the last century lies near the beginning of an unparalleled national -- and international -- fascination with the indigenous music of a single state. Kentucky has long figured prominently in our national sense of traditional music. Over the years, a diverse group of people -- reformers, enthusiasts, the musically literate and the musically illiterate, radicals, liberals, a.